Kenaikan C-Reactive Protein pada Remaja Gangguan Bipolar: A Systematic Review - Ulil Albab Habibah; Satria Akbar Putra Asmara; Triyana Indah Purwati; Nisrina Nabila (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The diagnosis of bipolar disorder (BD) in adolescents is often delayed due to reliance on subjective assessments, necessitating objective biomarkers such as C-reactive protein (CRP) to improve clinical accuracy. This systematic review aims to synthesize the latest findings on the role of CRP levels in adolescents with BD through analysis of various experimental studies. The systematic review was conducted in January 2026 through searches in Embase, PubMed, and ScienceDirect for studies from 2016 to 2025. Selection was performed according to PRISMA. Risk of bias was assessed using JBI Critical Appraisal Tools. A total of four experimental studies with a total of 3298 subjects met the criteria with low to moderate risk of bias. CRP levels in adolescents with Bipolar Disorder were found to be significantly elevated compared to the control group, especially during the symptomatic phase and periods of severe symptoms. CRP levels in adolescents with BD were found to be significantly elevated compared to healthy controls (p<0.001) and the anxiety disorder group, especially during the severe symptomatic phase. Additionally, high initial CRP levels significantly predicted longer recovery times (p=0.009). CRP is an effective state-dependent biomarker to support diagnostic accuracy, predict clinical course, and monitor the risk of cognitive decline in adolescents with BD.